2020
DOI: 10.1029/2019gl086313
|View full text |Cite
|
Sign up to set email alerts
|

Thermospheric Composition O/N Response to an Altered Meridional Mean Circulation During Sudden Stratospheric Warmings Observed by GOLD

Abstract: Observations from the recently launched Global‐Scale Observations of the Limb and Disk (GOLD) instrument on the geostationary SES‐14 communications satellite reveal a substantial response of the mean state of the thermosphere to the Sudden Stratospheric Warming (SSW) event in early January 2019. The observed O/N 2 column density depletion of more than 10% starts at the onset of the SSW, maximizes at the time of the stratospheric wind reversal, and recovers toward the end of the SSW. A connection between SSW an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

21
89
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(111 citation statements)
references
References 36 publications
21
89
1
Order By: Relevance
“…This enhanced poleward (and downward-not shown) flow driven at least in part by increased SW2 amplitudes between ∼115 and 150 km acts to adiabatically heat the lower thermosphere, especially at middle-to-high northern latitudes (see Figure 10). Further, this enhanced poleward (and downward) flow shown in Figure 8 coupled with enhanced equatorward (and upward) flow shown in Figure 6 between ∼90 and 110 km is consistent with previous modeling studies of enhanced lower atmospheric wave forcing on the meridional residual circulation (e.g., Miyoshi et al, 2015;Oberheide et al, 2020;Pedatella et al, 2016;Yamazaki & Richmond, 2013).…”
Section: Migrating Semidiurnal Tidesupporting
confidence: 91%
See 1 more Smart Citation
“…This enhanced poleward (and downward-not shown) flow driven at least in part by increased SW2 amplitudes between ∼115 and 150 km acts to adiabatically heat the lower thermosphere, especially at middle-to-high northern latitudes (see Figure 10). Further, this enhanced poleward (and downward) flow shown in Figure 8 coupled with enhanced equatorward (and upward) flow shown in Figure 6 between ∼90 and 110 km is consistent with previous modeling studies of enhanced lower atmospheric wave forcing on the meridional residual circulation (e.g., Miyoshi et al, 2015;Oberheide et al, 2020;Pedatella et al, 2016;Yamazaki & Richmond, 2013).…”
Section: Migrating Semidiurnal Tidesupporting
confidence: 91%
“…Ultimately, increased eastward small‐scale GWs dissipation/breaking during the January 2013 SSW/MC event appears to be the primary driver of light species depletions, with increased SW2 activity playing a modest role in the TIME‐GCM. With the recent launch of the Global‐scale Observations of the Limb and Disk (GOLD) mission studies using SABER H and GOLD O/N 2 (e.g., Oberheide et al, 2020) can be used to trace the effects of SSWs and MCs both vertically and horizontally within the atmosphere. These data provide the first opportunity to examine coupling from the high‐latitude stratosphere to the tropical thermosphere. Light species variability associated with SSW/MC may potentially affect the plasma population of the topside ionosphere and plasmasphere.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that the brightness depletion after day 25 (21 December 2018) may also be associated with the SSW. Pedatella et al (2016) suggested that an enhanced migrating semidiurnal tide (SW2) during SSW events is able to induce a global‐scale upward circulation and thereby a reduction of zonal mean O/N 2 ratio and electron densities (Liu & Roble, 2002; Oberheide et al, 2020; Shepherd et al, 1999). In addition, the intraseasonal variability (e.g., Sassi et al, 2019; Vergados et al, 2018) in the lower atmosphere could be responsible for the observed 60‐day oscillation in brightness as well.…”
Section: Resultsmentioning
confidence: 99%
“…The second temporal scale is associated with ionospheric oscillations with planetary wave time scales and observed as 2‐, 5‐ to 6‐, or 10‐ to 16‐day quasi‐periodic variations in peak electron density, peak height of the F region, and locations of the equatorial ionization anomaly (EIA) (Mo et al, 2014; Patra et al, 2014). The third temporal scale can last for 10–20 days or longer and is expressed as decreases in zonal and diurnal mean electron density and mean ionospheric peak height (Pancheva & Mukhtarov, 2011), decrease in thermospheric density (Liu et al, 2011; Yamazaki et al, 2015), and decrease in thermospheric O/N 2 ratio (Oberheide et al, 2020). These observational studies have stimulated considerable advances in understanding the physical mechanisms that link the state of the stratosphere to low‐latitude ionospheric variability.…”
Section: Introductionmentioning
confidence: 99%
“…These observational studies have stimulated considerable advances in understanding the physical mechanisms that link the state of the stratosphere to low‐latitude ionospheric variability. Three generally accepted mechanisms include (1) changes in the migrating and non‐migrating solar and lunar tides (Forbes & Zhang, 2012; Jin et al, 2012; Liu et al, 2010; Pedatella & Forbes, 2010), (2) increases in stratospheric tropical ozone during SSWs that lead to an enhancement in the migrating tide (Goncharenko et al, 2012; Limpasuvan et al, 2016; Siddiqui et al, 2019), and (3) reductions in the thermospheric O/N 2 ratio due to tidal dissipation (Oberheide et al, 2020; Yamazaki & Richmond, 2013). Superposition of these and other mechanisms that are still yet to be discovered creates highly variable conditions in the quiet‐time ionosphere‐thermosphere system that can be observed in multiple upper atmospheric parameters.…”
Section: Introductionmentioning
confidence: 99%